Renal Replacement Therapy with Regional Citrate Anticoagulation as an Effective Method to Treat Hypercalcemic Crisis. Issue 2 (March 2015) - Gradwohl-Matis, Ilse; Franzen, Michael; Seelmaier, Christina; Brunauer, Andreas; Dankl, Daniel; Dünser, Martin W.; Salmhofer, Hermann
<x xml:space="preserve">Abstract</x> Hemodialysis is considered the renal replacement technique of choice to control life-threatening hypercalcemia. In this case series, the experience with continuous venovenous hemodiafiltration (CVVHDF) with regional citrate anticoagulation to control five hypercalcemic crises in four patients is summarized. Overall maximum ionized and total calcium levels ranged from 1.72 to 2.01 mmol/L and 3.1 to 4.2 mmol/L, respectively. All patients presented with impaired consciousness, cardiac arrhythmias, or acute oliguria, despite therapy. Trisodium citrate was administered at 3 mmol/h (hourly calcium replacement 1.15–2.75 mmol). This allowed a controlled decrease in ionized calcium levels below 1.4 mmol/L within 4 hours (interquartile range [IQR], 2.5–10) and resolution of neurological symptoms within 15.5 hours (IQR, 12–22.8). The duration of CVVHDF was 1 day in those patients in whom hypercalcemia was the reason for admission. Four asymptomatic episodes of mild hypocalcemia occurred in two patients. No patient developed relevant abnormalities of serum sodium levels or pH, experienced cardiac arrhythmia, or required transfusion of blood products during CVVHDF. One patient with metastatic bronchial carcinoma experienced rebound hypercalcemic crisis 13 days after a 1 day session of CVVHDF with regional citrate anticoagulation. In conclusion, CVVHDF with regional citrate anticoagulation appears to be effective and potentially safe to rapidly normalize calcium levels in hypercalcemic crisis.